2000
DOI: 10.4049/jimmunol.164.10.5482
|View full text |Cite
|
Sign up to set email alerts
|

Impact of HIV-1 Infection on VH3 Gene Repertoire of Naive Human B Cells

Abstract: B cells of the largest Ig variable heavy chain gene (VH) family, VH3, are reportedly decreased in patients with late stage HIV-1 disease. This deficit may contribute to their impaired responses to infections and vaccines. We confirmed that the VH3 family was underrepresented in serum IgM proteins, with a 45% decrease in patients with advanced HIV-1 disease. However, the proportion of VH3 within VH(1–6) IgM mRNA from peripheral B cells did not differ from that of control subjects (mean ± SD, 57.1 ± 9.7 vs 61.1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
38
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 55 publications
6
38
0
Order By: Relevance
“…It may therefore play a role in the gp120-mediated increase in CD95 expression and CD95-mediated apoptosis in B cells. An increase in susceptibility to CD95 apoptosis may be involved in the depletion of peripheral B cells reported by several groups in HIV-infected patients (3,9,10,57). The gp120-induced decrease in membrane CD62L expression was dependent on CD4, CXCR4 triggering, and on the activation of G␣ i , p38 MAPK, and its cleavage by MMP.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…It may therefore play a role in the gp120-mediated increase in CD95 expression and CD95-mediated apoptosis in B cells. An increase in susceptibility to CD95 apoptosis may be involved in the depletion of peripheral B cells reported by several groups in HIV-infected patients (3,9,10,57). The gp120-induced decrease in membrane CD62L expression was dependent on CD4, CXCR4 triggering, and on the activation of G␣ i , p38 MAPK, and its cleavage by MMP.…”
Section: Discussionmentioning
confidence: 90%
“…As V H 3 genes are the key determinants of Abs specific for bacterial polysaccharide Ags, the depletion of V H 3-expressing B cells may contribute to the observed increase in the incidence of secondary infections in HIV-infected patients (19). Scamurra et al (10) recently showed in vivo that the depletion of peripheral V H 3-expressing memory B cells, but not of naive B cells, in HIV-infected patients involves gp120 binding.…”
Section: H Uman Immunodeficiency Virus-1 Infection Is Associatedmentioning
confidence: 99%
See 1 more Smart Citation
“…9,11 Further, alteration of this gene family homeostasis in the circulating B-cell repertoire is associated with disease states. [19][20][21][22] In recent work, long-lived plasma cells were shown to contain significantly fewer autoreactive B cells than the circulating IgG memory subset, and this difference was attributed to differential repertoire regulation within the two subsets. 23 Thus, although no mechanism for regulation of circulating human antibody repertoires has been identified, mounting indirect evidence, including the data presented in this report, suggests the presence of such regulation.…”
Section: Resultsmentioning
confidence: 99%
“…A role for humoral immunity in this process is supported by the common development of hypergammaglobulinemia in chronically infected individuals, associated with B cell hyperactivation, clonal expansions and deletions, and deficient costimulatory function. [1][2][3][4][5][6] It is unclear, however, if these abnormalities are the result of viremia and a direct effect of virus on B lymphocytes or, alternatively, mediated by long-term infectioninduced changes in T-cell subsets and cytokine production. To assess the early effect of HIV infection on the integrity of the peripheral B cell repertoires, we analyzed the B cellreceptor diversity in a longitudinal cohort of 10 affected individuals who had been treated with HAART immediately after diagnosis and 10 infected individuals who chose not to be treated.…”
mentioning
confidence: 99%